Immigrant families in contemporary society - Lansford, Jennifer E.; Deater-Deckard, Kirby D.; Bornstein, Marc H. (Duke series in child development and public policy., 2007)
How do some families successfully negotiate the linguistic, cultural, and psychological challenges of immigration, while others struggle to acculturate? This timely volume explores the complexities of immigrant family life in North America and analyzes the individual and contextual factors that influence health and well-being. Synthesizing cutting-edge research from a range of disciplines, the book addresses such key topics as child development, school achievement, and the cultural and religious contexts of parenting. It examines the interface between families and broader systems, including sc.